"That's Not Just Beautiful—That's Incredibly Beautiful!": The Adverse Impact of Inflated Praise on Children With Low Self-Esteem. (March 2014) - Brummelman, Eddie; Thomaes, Sander; Orobio de Castro, Bram; Overbeek, Geertjan; Bushman, Brad J.
In current Western society, children are often lavished with inflated praise (e.g., "You made an incredibly beautiful drawing!"). Inflated praise is often given in an attempt to raise children's self-esteem. An experiment (Study 1) and naturalistic study (Study 2) found that adults are especially inclined to give inflated praise to children with low self-esteem. This inclination may backfire, however. Inflated praise might convey to children that they should continue to meet very high standards—a message that might discourage children with low self-esteem from taking on challenges. Another experiment (Study 3) found that inflated praise decreases challenge seeking in children with low self-esteem and has the opposite effect on children with high self-esteem. These findings show that inflated praise, although well intended, may cause children with low self-esteem to avoid crucial learning experiences.